IMPROVEMENT OF THE INVESTMENT CLIMATE AS A MAIN CONDITION FOR THE ENHANCEMENT OF THE QUALITY OF LIFE IN RURAL AREAS - Aurelia LITVIN; Svetlana PETRASCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This work reflects results of the study on the improvement of the investment climate and the analysis of foreign direct investments in the economy of the Republic of Moldova. At present the basic priorities of the Ministry of Economy of the Republic of Moldova are the improvement of the investment climate in order to enhance the quality of life, the improvement of tools designed to attract foreign and local investors, as well as the promotion of local products in order to increase the competitiveness of economy. This is explained by the fact that investments increase the competitiveness of businesses, facilitate technology transfer, create new jobs and stimulate foreign trade, which are the basic elements in the process of development and implementation of policies aimed to attract investments and promote export.